Trans-ethnic kidney function association study reveals putative causal genes and effects on kidney-specific disease aetiologies - Andrew P. Morris (Nature Portfolio, 2019)
Estimated glomerular filtration rate (eGFR) is a measure of kidney function used to define chronic kidney disease. Here, Morris et al. perform trans-ethnic genome-wide meta-analyses for eGFR in 312,468 individuals and identify novel loci and downstream putative causal genes.